HUBUNGAN KERAPATAN MANGROVE TERHADAP KEPADATAN POPULASI IKAN GELODOK (FAMILI: GOBIIDAE) DI DESA PULAU SEMBILAN KABUPATEN LANGKAT SUMATERA UTARA The Relationships Mangrove Density with Population Density of Mudskipper (Family: Gobiidae) in the Sembilan Isl - Bill Maulana Bidawi; Yunasfi Djayus; Desrita Desrita (AQUACOASTMARINE, 2017)
Utilization of Mangrove Ecosystem as land conversion resulting decline in the productivity of the mangrove ecosystem. The transition function of the mangrove ecosystem damage and disrupt the microbial life in it. One of which is a Mudskipper. The research aims to determine how the population density of Mudskipper and how the relationship of mangrove density to the population density of Mudskipper. The research was conducted for two months from March to April 2016 at the mangrove ecosystem in the Sembilan Island village. The research used purposive random sampling method. There are three kind of fish can be found in those areas, which are Periophthalmus chrysospilos, Periophthalmus gracilis, and Boleophthalmus boddarti. The results of this research is the highest population density of Mudskipper are found at station III with a value of 7400 Ind/ha and lowest were in station IV with a value of 2600 Ind/ha. The highest density of mangrove are found at station 4 with a value of 4800 Ind/ha and lowest were in station III with a value of 4066 Ind/ha and categorized good. Relationship between the mangrove density and the population density of Mudskipper exhibits a positive correlation with a value of 0,941.Key Words : Identification, Mangrove, Mudskipper, Population Density.